Configuração discursiva da recepção polêmica no Facebook de uma peça publicitária na Internet - Menino, Patrícia de Jesus (2019)
The objective of this study is to analyze how are configured discursively the comments registered in Facebook to the advertising placed in the social media by Loja Marisa, for occasion of the Mother’s Day in the year of 2017. We analyzed 200 comments identified by the algorithm as the most relevant, because they had the largest number of interactions (likes or answers). For the analysis, we initially classified these comments into two groups: the one that expressed contrariety to the advertising piece, constituted by the great majority of comments, and the one that was in favor of it. The analysis was made, having as theoretical orientation, fundamentals of the greimasian semiotic theory. The general objective of the work was to make a discursive configuration of these comments, with a particular focus on their polemical character. The specific objectives were: to characterize the statements from the point of view of its enunciative construction; to describe the argumentative strategies used by internauts in the defense of their points of view; explicit the thematic and figurative networks that structure the statements/comments. Thus, we could conclude that the comments, for the most part, were to disapprove the advertising campaign for Mother's Day at Loja Marisa. In these anti-advertising comments, there is the predominance of a unilateral communication, where the enunciator imperiously manifests his condemnation of the advertisement, expresses this contrariety through thematic-figurative paths of disqualification and reprisal often characterized by the traces of hatred and intolerance. These comments could also be classified into two major themes that caused this contrariety: the theme of disrespect for the dead – being all those who repudiated the advertising piece for interpreting it as an act of disrespect to the figure of Dona Marisa, mother, ex-first lady and deceased in february of that year; and the theme of the political offense – being all the comments they interpreted as misconduct by Loja Marisa to use their brand and their space for publicity, to make a speech that encouraged political discussion in a derogatory way, instigating voters.